1981
DOI: 10.1111/j.1365-2818.1981.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Specimen heating during sputter‐coating

Abstract: It is possible to sputter thin films of gold on to surfaces of frozen biological specimens at very low temperatures ( < 120 K) without untoward effects from heating. This is achieved by using permanent magnets to confine the plasma and thus to minimize the energy required to give a reasonable sputtering yield. The system described uses only 250 V at 12-15 mA to give 15 nm films within 2-3 min. It is shown, from theory portraying 'worst-case' conditions, that the specimen temperature could not increase by more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Earlier studies by Echlin et al (1980Echlin et al ( , 1982, Echlin (1981), Robards et al (1981 and Nockolds et al (1982) have shown that there is a decrease in thin film particle size and hence an increased spatial resolution on specimens, if sputter coating is carried out at decreased cathode voltages. The earlier studies were carried out in the range 400-2000 V (Echlin et al, 1982), 250-760 V (Robards et al, 1981) and 200-350 V (Nockolds et al, 1982) and in all instances it was found that as the cathode voltage was lowered there was also a decrease in the potential thermal load into the specimen. These procedures allowed thermolabile specimens such as low melting point hydrocarbon waxes, plastic films and frozen hydrated specimens to be coated without any apparent damage to the samples.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier studies by Echlin et al (1980Echlin et al ( , 1982, Echlin (1981), Robards et al (1981 and Nockolds et al (1982) have shown that there is a decrease in thin film particle size and hence an increased spatial resolution on specimens, if sputter coating is carried out at decreased cathode voltages. The earlier studies were carried out in the range 400-2000 V (Echlin et al, 1982), 250-760 V (Robards et al, 1981) and 200-350 V (Nockolds et al, 1982) and in all instances it was found that as the cathode voltage was lowered there was also a decrease in the potential thermal load into the specimen. These procedures allowed thermolabile specimens such as low melting point hydrocarbon waxes, plastic films and frozen hydrated specimens to be coated without any apparent damage to the samples.…”
Section: Introductionmentioning
confidence: 97%
“…This can in turn distort the morphology of the specimens as demonstrated with polymer substrates (Bodo and Sundgren 1986). According to some authors (Echlin 1978, Ingram 1976, Robards 1981, another source of heat damage is radiation from the target. This heat, which is of long wavelength, could only damage a specimen which is placed quite close to the target.…”
Section: Magnetron-sputtered W Films (Target To Specimen Distance 18 mentioning
confidence: 99%